Risk-Assessment-Based Optimization Favours the Development of Albumin Nanoparticles with Proper Characteristics Prior to Drug Loading - Gábor Katona; Bence Sipos; Ildikó Csóka (MDPI AG, 2022)
Albumin nanocarrier research and development is a challenging area in the field of personalized medicine and in providing advanced therapeutic solutions. Albumin as a biocompatible, nonimmunogenic, and non-toxic protein carrier that can be exploited to conjugate drugs with poor bioavailability to improve on this feature. With many different perspectives and desired target profiles, a systematic structural approach must be used in nanoparticle development. The extended Research and Development (R&D) Quality by Design thinking and methodology proved to be useful in case of specific nanoparticle development processes before. However, the coacervation method is the most frequently applied preparation method for HSA nanoparticles; there is a lack of existing research work which has directly determined the influence of process parameters, control strategy, or design space. With a quality-management-driven strategy, a knowledge space was developed for these versatile nanoparticles and an initial risk assessment was conducted on the quality-affecting factors regarding the coacervation method, followed by an optimization process via Plackett-Burman and Box-Behnken experimental design. As a result of screening the effect of process variables on the fabrication of HSA nanoparticles, an optimized colloidal drug delivery system was engineered with desired nanoparticulate properties.